Efficient conversion of carbohydratesto ethoxymethylfurfural and levulinic acid ethyl ester under the catalysis of recyclable DMSO/Brønsted acids. Issue 9 (29th May 2015) - Liu, Jitian; Tang, Yu; Fu, Xu
Abstract : This paper presents a novel and environment‐friendly process for the dehydration of carbohydrates to ethoxymethylfurfural (EMF) and levulinic acid ethyl ester (LAEE) under the catalysis of DMSO/H2SO4. The catalyst was recycled efficiently and easily over seven times without any significant loss in fructose conversion. For the conversion of fructose and inulin, EMF and LAEE were obtained in 83% and 80% total yields, respectively. The effects of catalyst loading, reaction temperature, and reaction time on dehydration reaction were investigated.